1986
DOI: 10.1126/science.231.4739.717
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Todorokite

Abstract: Todorokite of chemical composition (Mg(0.77)Na(0.03))(Mg(0.18)Mn(2+)(0.60)Mn(4+)(5.22)22) O(12).3.07 H(2)O was synthesized by a two-step procedure. First, sodium birnessite was synthesized and magnesium was exchanged for sodium to form magnesium birnessite, which was autoclaved under a saturated steam pressure at 155 degrees C for 8 hours to form well-crystallized todorokite. Synthesized todorokite particles consisted of fibers extending from a central plate. The plate itself was made of twinned fibers forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(182 citation statements)
references
References 5 publications
11
171
0
Order By: Relevance
“…Although todorokite in the natural form is a hydrated manganese oxide with impurities, the todorokite-type manganese oxide has been synthesized hydrothermally as a single-phase material [10][11][12][13]. Golden et al have reported a synthetic todorokite-type manganese oxide that was prepared by the hydrothermal treatment of Mg 2+ -exchanged birnessite-type manganese oxide [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although todorokite in the natural form is a hydrated manganese oxide with impurities, the todorokite-type manganese oxide has been synthesized hydrothermally as a single-phase material [10][11][12][13]. Golden et al have reported a synthetic todorokite-type manganese oxide that was prepared by the hydrothermal treatment of Mg 2+ -exchanged birnessite-type manganese oxide [10].…”
Section: Introductionmentioning
confidence: 99%
“…Layered buserites with interlayer transition-metal cations were previously known only as precursors for todorokites. [8][9][10] Hollandites with interstitial transition metals are obtainable through ion exchange of K + in cryptomelane, but these substitution reactions are incomplete. [17,18] Indeed, only one other purely transition-metal hollandite, Aghollandite, has been reported to date [19][20][21] and none are known with transition-metal cations having charges greater than 1+.…”
Section: Cr-holl(cr)mentioning
confidence: 99%
“…When a divalent cation (Mg 2+ ) is substituted for interstitial Cr 3+ in the buserite precursor, Mg-buse(Cr), hydrothermal treatment produces the expected Mg-todo(Cr). [8][9][10][11][12] …”
Section: Influence Of Cr 3+ On Hollandite Formationmentioning
confidence: 99%
See 2 more Smart Citations